Bentuk dan Gerak Wayang Kaca dalam Pentas Wayang Tantri Sebuah Kreativitas Seni Modern Berbasis Kebudayaan Lokal - I Dewa Ketut Wicaksandita (PANTUN, 2019)
Wayang Tantri is one of Wayang arts which is still productive and creative in performing Wayang Kaca (glass wayang) in some scenes of their performance. The visual of the performance is the re?ection of light with the motif of forms and paterns of the traditional Balinese leather puppet(wayang kulit). The creation is conducted by I Wayan Wija by enriching the movements of wayang tetikesan adapted from Balinese leather puppet. The subject of the analysis is wayang kaca in the play of Wayang Tantri of I Wayan Wija’s Sang Aji Dharma Kepastu in Bali record. The aim of thispaper is to identify the form and movement of Wayang. The analysis is explored within local ideas in the form of the wayang. The data are collected through observation, interview, and document study to the video of the subject of the analysis which is more or less about 2 hours. The theory applied is Instrumental Aesthetics and Estetika Pedalangan. The result shows that wayang kaca is Dalang Wija’s thought on the manifestation of Dewa (God) which is re?ected in the form of light (dev) in the performance. The basic materials are created into various forms of Balinese wayang characterssuch as Barong, dewa-dewi, penari baris, etc. The tetikesan model applied in wayang kaca is adapted movements from traditional wayang comprising “gerak wantah” and “gerak maknawi.Keywords: Wayang Tantri, wayang Kaca, form, movement.